TINJAUAN YURIDIS PERKAWINAN PADA GELAHANG DALAM PERSPEKTIF HUKUM POSITIF INDONESIA - Krisna Ananda Putra; Diangsa Wagian (Fakultas Hukum Universitas Mataram, 2021)
This research aims to determine the implementation and legal status of Gelahang according to Indonesian law and its consequences to the inheritance. Type of this research is normative legal research using statutes and conceptual approach. Research report indicates that the implementation of this marriage is not only involve the couple but also the agreement of both families as they are hold Kapurusa status in their domicile. Related to the legal status of Gelahang according to marriage law is legal since there is no regulation being break. The inheritance of carried out based on the agreement made in Pasobayan Mawarang.